Transformasi Pedagogi Digital dalam Pembelajaran Pendidikan Agama Islam: Analisis Penggunaan Media Visual dan Gamifikasi di SMAN 2 Tenggarong - Dwi Juliyanto; Sahrur Rhamadon; Diana Anggraini; Chusnul Chotimah; Julia Muryani; Mubarok Mubarok (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The advancement of digital technology has significantly transformed education, including the implementation of Islamic Religious Education (PAI) learning. This study aims to analyze the transformation of digital pedagogy through the use of visual media and gamification in PAI learning at SMAN 2 Tenggarong. The research employed a descriptive qualitative approach, with data collected through observations and interviews.The findings show that teachers utilize various digital learning technologies, including Smart Boards, Canva presentations, Google Classroom, and interactive quiz applications to support learning. Teaching activities include interactive lectures, literacy activities, group discussions, ice-breaking sessions, and gamification-based assessments. These strategies enhance students’ enthusiasm, participation, and engagement throughout the learning process.Visual media help students understand learning materials more clearly and attractively, while gamification creates an enjoyable learning environment that encourages active participation. Although challenges such as internet connectivity and inappropriate gadget use remain, teachers address them through classroom rules and supervision. Overall, digital pedagogy positively improves students’ interest, participation, and understanding in Islamic Religious Education learning.